Optimizing the manure substitution rate based on phosphorus fertilizer to enhance soil phosphorus turnover and root uptake in pepper (Capsicum) - Sun, Kai; Cui, Yutao; Sun, Linglulu; Wei, Bingli; Wang, Yuan; Li, Shunjin; Zhou, Chengxiang; Wang, Yixia; Zhang, Wei (Frontiers in Plant Science, 2024)
In contemporary agriculture, the substitution of manure for chemical fertilizer based on phosphorus (P) input in vegetable production has led to a significant reduction in P fertilizer application rates, while, the effect of manure substitution rates on soil P transformation and uptake by root remain unclear. This research conducts a pot experiment with varying manure substitution rates (0%, 10%, 20%, 30%, 40%, 50%, 75% and 100%) based on P nutrient content to elucidate the mechanisms through which manure substitution affects P uptake in pepper. The result showed that shoot and root biomass of pepper gradually increased as manure substitution rate from 10% to 40%, and then gradually decreased with further increases in the substitution rate. Soil alkaline phosphatase activity and arbuscular mycorrhizal (AM) colonization gradually increased with manure substitution rates improvement. Specifically, when the substitution rate reached 30%-40%, the alkaline phosphatase activity increased by 24.5%-33.8% compared to the fertilizer treatment. In contrast, phytase activity and the relative expression of phosphate transporter protein genes in the root system was declined after peaking at 30% manure substitution.Additionally, soil available P remained moderate under 30%-40% substitution rate, which was reduced by 8.6%-10.2% compared to that in chemical fertilizer treatment, while microbial biomass P was comparable. In the current study, soil labile P similar to or even higher than that in chemical fertilizer treatment when the substitution rate was ≤40%. Correlation heatmaps demonstrated a significant and positive relationship between soil available P and factors related to labile P and moderately labile P. This finding suggested that substituting 30%-40% of chemical P with manure can effectively enhance root length, AM colonization, soil enzyme activity, soil labile P, and consequently improve P uptake in pepper.These findings provide valuable insights for future organic agricultural practices that prioritize P supply, aiming to standardize organic P management in farmland and achieve high crop yields and maintain soil health.